The extra-territorial paradox of voting: the duty to vote in extra-territorial elections. Issue 2 (23rd February 2017) - Knott, Eleanor
ABSTRACT: The question of why individuals vote, the so-called "paradox of voting", has been a crucial debate within political science, conceived deductively as an interaction between costs, benefits, and, as some argue, duties. This article situates the question of why individuals vote within the context of extra-territorial elections, focusing on how and why those who acquire citizenship kin-states participate in kin-state elections following citizenship acquisition, while continuing to reside outside of the kin-state. The article uses the case of newly acquired Romanian citizens in Moldova, who have never resided in nor intend to reside in Romania, to unpack whether, how, and why individuals acquiring Romanian citizenship in Moldova vote in Romanian elections. The article uses an interpretive and inductive approach to explore from the bottom up both the experiences of and motivations for political participation of extra-territorial citizens. The article finds, unexpectedly, how those acquiring Romanian citizenship in Moldova are motivated by a duty to participate. Overall, the article argues for a relational and reciprocal understanding of citizenship and voting, which focuses on the relationship between the kin-state, facilitating citizenship as a right, and the kin-citizen, performing their duty to vote.